PENGARUH DISIPLIN KERJA, BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PT ADI SARANA ARMADA TBK (ASSA LOGISTICS) SEMARANG JAWA TENGAH - Anggraini Hesti Novita; Justita Dura; Agus Rahman Alamsyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to analyze the effect of work discipline, organizational culture on employee performance and work motivation as intervening variables at PT Adi Sarana Armada Tbk (ASSA Logistics) Semarang, Central Java. The data used in this research is primary data obtained from the results of distributing questionnaires. In this research, the sample was determined using a non-random sampling method (non-probability sampling) with a purposive sampling procedure with a sample size of 50 people. The research data was processed in a quantitative descriptive manner using path analysis techniques and using Smart PLS 3.29. The results of the study concluded that (1) work discipline had a positive and insignificant effect on work motivation, (2) organizational culture had a positive and significant effect on work motivation, (3) work discipline had a positive and not significant effect on employee performance, (4) organizational culture had a positive effect and significant on employee performance, (5) work motivation has a positive and significant effect on employee performance, (6) work motivation has a positive and insignificant effect as an intervening variable that is able to mediate work discipline on employee work performance, (7) work motivation has a positive and significant effect as a capable intervening variable mediates organizational culture on employee work performance.